The Genetics and Biology of Disc1—An Emerging Role in Psychosis and Cognition - Porteous, David J.; Thomson, Pippa; Brandon, Nicholas J.; Millar, J. Kirsty (Biological psychiatry (1969), 2006)
In the developing field of biological psychiatry, DISC1 stands out by virtue of there being credible evidence, both genetic and biological, for a role in determining susceptibility to schizophrenia and related disorders. We highlight the methodologic paradigm that led to identification of DISC1 and review the supporting genetic and biological evidence. The original finding of DISC1 as a gene disrupted by a balanced translocation on chromosome 1q42 that segregates with schizophrenia, bipolar disorder, and recurrent major depression has sparked a number of confirmatory linkage and association studies. These indicate that DISC1 is a generalizable genetic risk factor for psychiatric illness that also influences cognition in healthy subjects. DISC1 has also been shown to interact with a number of proteins with neurobiological pedigrees, including Ndel1 (NUDEL), a key regulator of neuronal migration with endo-oligopeptidase activity, and PDE4B, a phosphodiesterase that is critical for cyclic adenosine monophosphate signaling and that is directly linked to learning, memory, and mood. Both are potential “drug” targets. DISC1 has thus emerged as a key molecular player in the etiology of major mental illness and in normal brain processes.